First Case of Tularemia Reported in Portugal: Probably of Imported Origin - Lopes de Carvalho, I (2018)
The authors report the case of a 47-year-old man who walked in the countryside on the island of Bornholm, during the summer period. Three days later, fever, myalgias and adynamia began. The serological tests, Real-time PCR and isolation of the bacteria from the culture of lymph biopsy confirmed the presence of Francisella tularensis subsp. holarctica.